2010
DOI: 10.3758/s13421-010-0017-4
|View full text |Cite
|
Sign up to set email alerts
|

Experience with proactive interference diminishes its effects: mechanisms of change

Abstract: In three experiments, we examined the mechanisms by which prior experience with proactive interference (PI) diminished its effects. Cued recall tasks conforming to an A-B, A-D paradigm were used to induce PI effects. Experiment 1 showed that reduced PI was not due to a reduction in attention to the source of PI. Experiment 2 revealed that participants' awareness of PI effects on memory performance increased with experience, resulting in a shift in encoding processes. Experiment 3 demonstrated that changes in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 24 publications
0
15
1
Order By: Relevance
“…Overall, then, the trial-by-trial method for obtaining responses and free/forced decisions would seem to be the preferable methodology and may partly explain why it is being increasingly adopted in research examining strategic accuracy regulation (e.g., Higham, 2007, Exp. 2;Jacoby, Wahlheim, Rhodes, Daniels, & Rogers, 2010;Wahlheim & Jacoby, 2011) Returning to the present results, the fact that categorization decreased rather than increased the HR marks a difference between our results and those obtained in overtrecognition studies. One potential cause of the difference is that studies that have demonstrated an increase to the HR from categorization have used old/new recognition.…”
Section: Resolution Versus Overt Recognitioncontrasting
confidence: 89%
“…Overall, then, the trial-by-trial method for obtaining responses and free/forced decisions would seem to be the preferable methodology and may partly explain why it is being increasingly adopted in research examining strategic accuracy regulation (e.g., Higham, 2007, Exp. 2;Jacoby, Wahlheim, Rhodes, Daniels, & Rogers, 2010;Wahlheim & Jacoby, 2011) Returning to the present results, the fact that categorization decreased rather than increased the HR marks a difference between our results and those obtained in overtrecognition studies. One potential cause of the difference is that studies that have demonstrated an increase to the HR from categorization have used old/new recognition.…”
Section: Resolution Versus Overt Recognitioncontrasting
confidence: 89%
“…It is likely that training either type of recollection mechanism could effectively remediate age-related deficits in proactive interference. Studies have shown that experience with proactive interference can diminish its effects either by tightening retrieval constraints, so that competitors are less likely to come to mind (Jacoby, Wahlheim, Rhodes, Daniels, & Rogers, 2010; Wahlheim & Jacoby, 2011), or by increasing the probability of targets and competitors being recalled together (Postman, 1964). …”
Section: Methodsmentioning
confidence: 99%
“…This confusion regarding the origins of the RN probe is also reflected in metacognitive measures. Specifically, confidence ratings for correct rejections of the RN probe are typically lower than those for the NRN probe, and false alarms may reflect the presence of high-confidence intrusion errors (Jacoby, Wahlheim, Rhodes, Daniels, & Rogers, 2010;Wahlheim & Jacoby, 2011).…”
mentioning
confidence: 99%